PRELIMINARY SESSION JUDGE IMPORTANT ACTOR AND GUARANTEE OF DUE JUDICIAL PROCESS AFTER COMPLETION OF PRELIMINARY INVESTIGATIONS PHASE - Prifti, Arben (International Journal of Legal and Social Order, 2025)
Constitutional reform (A.Vorpsi, A.Anastasi, G.Ibrahimi, S.Berberi, 2016)and that in Justice (Code of Criminal Procedure, 2017) of 2016 in Albania, brought the need for intervention and changes in the Criminal Procedure Code. A new change in this Code is the figure of the Judge of the Preliminary Session, as a new subject in the criminal process, at the stage of completion of preliminary investigations. This new procedural institute, placed between the prosecutor and the judge of the foundation, serves as a filter to control the procedural actions of the prosecutor, carried out during the phase of the preliminary investigations, if they are complete and final, paving the way for the trial of the case. nȅ foundation. In this work, research, analytical and comparative methods were used, with the aim of highlighting the problems that have to do with the procedural subject of the Judge of the Preliminary Session, as well as the hypotheses with the questions that are asked. The jurisprudence of the cases of judicial practice of the Courts of the General Jurisdiction of the Appeal and of the First Instance, the Supreme Court and the Constitutional Court deal with the competencies and functions of the Judge of the preliminary session as well as the problems that arise during at this stage of the criminal proceedings.